2017
DOI: 10.1177/2165143417741477
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Status of Transition-Focused Content Within Educator Preparation Programs

Abstract: Almost two decades since the last study of how educator preparation programs (EPPs) offer transition-related content to preservice teachers, this study sought to understand if the educator preparation landscape has changed. Given the impact of well-prepared secondary educators on student transition outcomes, reexamining the status of transition-related content within teacher education was warranted. Thus, the primary purpose of this study was to query a national sample of EPPs regarding the specific transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
(33 reference statements)
0
28
1
Order By: Relevance
“…Furthermore, results of this study do not necessarily align with the findings from Morningstar et al (2017) indicating that SEAs and IHEs have different information related to certification and licensure options offered by their states. This inconsistency suggests the need for increased collaboration among various stakeholders in transition-related personnel preparation, including SEAs, IHEs, and SVRAs (Plotner & Simonsen, 2017).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, results of this study do not necessarily align with the findings from Morningstar et al (2017) indicating that SEAs and IHEs have different information related to certification and licensure options offered by their states. This inconsistency suggests the need for increased collaboration among various stakeholders in transition-related personnel preparation, including SEAs, IHEs, and SVRAs (Plotner & Simonsen, 2017).…”
Section: Discussioncontrasting
confidence: 94%
“…First, insufficient funding is available to support preservice and in-service personnel preparation of special education teachers in general, and secondary special education teachers in particular (Mazzotti, Rowe, Cameto, Test, & Morningstar, 2013; National Coalition on Personnel Shortages in Special Education and Related Services, 2017; Plotner & Simonsen, 2017). Next, a lack of collaboration between SEAs, LEAs, and institutions of higher education (IHE) exists relative to providing credentialing options for special education teachers (Morningstar, Kleinhammer-Tramill, Hirano, Roberts-Diehm, & Teo, 2017; Muller, 2010). Many states have limited credentialing options to (a) support specialization in specific special education areas (e.g., secondary transition) and (b) offer alternative routes to licensure (National Coalition on Personnel Shortages in Special Education and Related Services, 2017).…”
mentioning
confidence: 99%
“…Next, Phase 2 participants discussed the importance of faculty expertise related to the development of transition personnel preparation programs. Morningstar et al (2017) surveyed 145 faculty members from 140 educator preparation programs and found 45% of respondents reported having a faculty member who specialized or conducted research in the area of secondary transition. The number of faculty specializing in transition may contribute not just to the availability of transition-related coursework but also to developing OSEP-funded transition preparation programs.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Because university teacher preparation programs are driven by federal and state policies and priorities, it is important to be able to evaluate special educators’ knowledge and skills related to providing transition services to students with disabilities so that policy makers can be informed of additional needs in their states (Morningstar & Clavenna-Deane, 2014). Most preservice teacher preparation programs for special educators do not provide the level of training needed to effectively plan and deliver transition services to students with disabilities (Benitez, Morningstar, & Frey, 2009; Morningstar, Hirano, Roberts-Dahm, Teo, & Kleinhammer-Tramill, 2018). Indeed, in-service training seems to be the primary method special education teachers receive information on transition planning and implementation (Benitez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%